2001
DOI: 10.1192/bjp.179.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term treatment with antipsychotics on serum leptin levels

Abstract: Elevation of leptin levels induced by chronic antipsychotic treatment can be attributed to weight gain, but other mechanisms could be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 19 publications
3
43
2
Order By: Relevance
“…Consistent with the report by Herran et al (2001), these results do not support hypotheses concerning impaired leptin secretion or leptin resistance in treated schizophrenia patients compared to healthy controls. Owing to continuing problem of increased prevalence of overweight and obesity in mental illnesses like schizophrenia, and the known impact of obesity on long-term survival, future studies of satiety signals are needed in order to improve the health of patients with mental illness.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Consistent with the report by Herran et al (2001), these results do not support hypotheses concerning impaired leptin secretion or leptin resistance in treated schizophrenia patients compared to healthy controls. Owing to continuing problem of increased prevalence of overweight and obesity in mental illnesses like schizophrenia, and the known impact of obesity on long-term survival, future studies of satiety signals are needed in order to improve the health of patients with mental illness.…”
Section: Discussionsupporting
confidence: 52%
“…Kraus et al (2001) reported lower plasma leptin levels in schizophrenia patients compared to adiposity-matched healthy controls, using the indirect adiposity measure of body mass index (BMI), arguing against leptin resistance and instead for the possibility of a decrease in leptin secretion or increased leptin clearance in this patient population. In contrast, Herran et al (2001) recently reported no difference in plasma leptin levels between treated schizophrenia patients and age, gender, and BMImatched healthy controls. Recently, Zhang et al (2004) described increases in leptin levels after antipsychotic associated weight gain, but the study was not designed to assess if the observed increases in leptin secretion were appropriate for the amount of adiposity gained during treatment.…”
Section: Introductionmentioning
confidence: 89%
“…Given our inability to detect inappropriate plasma leptin levels in antipsychotictreated patients in comparison to adiposity-matched controls, the case for undertaking these subsequent studies is weakened (Haupt et al, 2005). As stated in our paper, along with the recent report by Herran et al, evidence does not currently support the hypothesis that leptin regulation in schizophrenia patients during antipsychotic treatment, as compared to leptin regulation in untreated healthy controls, is due to impaired leptin secretion or leptin resistance (Haupt et al, 2005;Herran et al, 2001).…”
Section: Sircontrasting
confidence: 62%
“…Raised leptin and subsequent downregulation of hypothalamic leptin receptors or altered transport dynamics could explain the weight gain and diabetes in patients taking certain antipsychotics (72). Against this are the results of a study comparing leptin levels in 59 patients with chronic schizophrenia with those from a group of healthy subjects matched for sex, age, and BMI (79). There was no difference between leptin levels in patients taking chronic antipsychotic medication (37 conventional and 17 atypical) and matched control subjects.…”
Section: Leptinmentioning
confidence: 99%